2017
DOI: 10.1007/s00414-017-1650-2
|View full text |Cite
|
Sign up to set email alerts
|

Wound morphology in contact shots from blank cartridge handguns: a study on composite models

Abstract: It is a well-known fact that blank cartridge guns can cause penetrating and even fatal injuries when discharged in contact or at very close ranges. In these cases, the gas jet perforates the skin leaving an entrance wound similar to that from a conventional gun. In order to investigate the wound morphology in contact shots from blank firearms, test shots were fired at composite models of pig skin and gelatin blocks using three different calibre 9-mm blank cartridge handguns (two pistols and one revolver) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 33 publications
0
13
2
Order By: Relevance
“…From a ballistic aspect, BCs act as low-energy weapons, mostly in civilian use. The differential diagnosis between conventional ammunition and BC injury is very complex and almost impossible (2,4,5). This was the case in our report.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…From a ballistic aspect, BCs act as low-energy weapons, mostly in civilian use. The differential diagnosis between conventional ammunition and BC injury is very complex and almost impossible (2,4,5). This was the case in our report.…”
Section: Discussionmentioning
confidence: 61%
“…When a BC is fired, the gas jet that emerges in an explosion in the barrel acts as a bullet at close or contact range. This pressure or invisible bullet can be powerful enough to penetrate the soft tissue and even bones (2,5). Considering the skin defect and the entrance wound in our case, we think that a 9 mm cartridge was used, although we did not have any ballistic information because the criminal and gun could not be seized.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Contact shots with 9 mm Blank cartridges fired with two blank firing pistols and one revolver on pig skin and ballistic gelatin showed that the powder gases penetrated the skin and the soft tissue simulant for 2.2 to 6.1 cm. Particles of the pig skin were found in the radial cracks of the gelatin [ 167 ].…”
Section: Wound Ballisticsmentioning
confidence: 99%
“…Tausch et al also demonstrated the danger posed by blank ammunition to human bodies and advocated for stricter legal regulations in Germany already in 1974 [7]. More recent studies employing ballistic gelatin models with focus on wound morphology were published for instance by Schyma & Schyma [8] and Pircher et al [9]. However, systematic research involving molecular ballistic analyses of biological traces created by blank cartridge gun shots at biological targets has not been performed so far with the exception of a single study analyzing traces of backspatter inside 20 guns after fatal contact shots to the head, that included a .380 revolver described as a blank cartridge gun from which sufficient trace material for STR typing could be retrieved [10].…”
Section: Introductionmentioning
confidence: 99%